2017
DOI: 10.1186/s12934-017-0634-8
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of a novel antifungal chitinase identified by functional screening of a suppressive-soil metagenome

Abstract: BackgroundThrough functional screening of a fosmid library, generated from a phytopathogen-suppressive soil metagenome, the novel antifungal chitinase—named Chi18H8 and belonging to family 18 glycosyl hydrolases—was previously discovered. The initial extremely low yield of Chi18H8 recombinant production and purification from Escherichia coli cells (21 μg/g cell) limited its characterization, thus preventing further investigation on its biotechnological potential.ResultsWe report on how we succeeded in producin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 60 publications
2
30
0
Order By: Relevance
“…Elevated levels of chitinases have been reported in a variety of diseases including infections, chronic inflammation, and degenerative disorders [ 39 , 40 ]. Recent studies reported that CHIT1 play a role as antifungal and antibacterial activity [ 41 , 42 , 43 , 44 , 45 ]. We also demonstrated an enzymatic activity of CHIT1 in FSM that can partially explain its anti-microbial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of chitinases have been reported in a variety of diseases including infections, chronic inflammation, and degenerative disorders [ 39 , 40 ]. Recent studies reported that CHIT1 play a role as antifungal and antibacterial activity [ 41 , 42 , 43 , 44 , 45 ]. We also demonstrated an enzymatic activity of CHIT1 in FSM that can partially explain its anti-microbial activity.…”
Section: Discussionmentioning
confidence: 99%
“…Strain engineering to increase monoterpene precursor production has recently led to significant improvements in geraniol titers. (Jiang et al, 2017; Zhao et al, 2017). The G8H-mediated ω-hydroxylation of geraniol at C-8 was described as a major pathway bottleneck in S. cerevisiae due to poor activity of the P450 (Brown et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Culex quinquefasciatus became susceptible to the Bs treatment when Chitinase AC was overexpressed in B. sphaericus (Cai et al, 2007). In addition to the insecticidal property, chitinases can also inhibit fungus by destroying chitinous cell wall structure (Berini et al, 2017;Singh and Arya, 2019;Zarei et al, 2011). S. marcescens has been tested to be used against plant fungal pathogen due to its fungicidal properties (Purkayastha et al, 2018) making it an interesting candidate to be used against several classes of agricultural diseases.…”
Section: Discussionmentioning
confidence: 99%